The Conceptual Pattern of Fascist Ideology - Carlos Manuel Martins (Locus, 2022)
In spite of all the definitions of fascism that were presented in the last decades and the “consensus” that was created around the definition proposed by Roger Griffin (which focuses on the ultranationalist and palingenetic core of fascism), authors like Michel Dobry have criticized the tendency to opt for what they see as “essentialist” approaches and to worry too much with classifications. Nevertheless, I argue that, although the more dynamic aspects of fascist ideology must be kept in mind, definitions and classifications are a necessary component of the work of the historian that tries to make sense of the era of fascism. For this reason, I here have the goal of arriving at a new definition of fascism by making use of the conceptual morphological approach, put forward by Michael Freeden, which has never been systematically applied to the study of fascism and can lead us to new and interesting conclusions about the nature of this ideology. This essay is, thus, a reassessment of a research that I previously carried out and shall be read as a refined version of that study, which tried to define fascism through the core concepts that are part of its conceptual pattern. As it is made clear in the text, the concepts that I believe to be central to fascism are: Nation, State, Synthessis, Revolution, Authority and Violence.